FLUENT & FEARLESS: DEVELOPING REAL-LIFE ENGLISH COMMUNICATION COMPETENCE - Sudirman, Sudirman; Sutrisno, Supadi Bambang; Oktafiani, Susi; Giyanto, Giyanto; Anggraini, Desi (JOLADU: Journal of Language Education, 2025)
This study aims to develop students’ real-life English communication competence through communicative, multimodal, and practice-oriented instructional strategies. The research addresses the persistent challenges faced by Indonesian EFL learners, particularly low speaking confidence, high anxiety, and limited willingness to communicate. A mixed-method classroom-based research design was employed involving 32 undergraduate EFL students. Data were collected through pre- and post-speaking tests, communicative competence rubrics, questionnaires on Willingness to Communicate (WTC), classroom observation, and semi-structured interviews. The intervention integrated role-play, multimodal tasks, gamified communicative projects, and structured real-life speaking simulations over eight weeks. Findings indicate significant improvement in students’ fluency, pronunciation accuracy, sociolinguistic appropriateness, and strategic competence. Students demonstrated increased confidence and reduced speaking anxiety. Quantitative results show a 28% increase in speaking performance scores and a 35% rise in WTC indicators. Qualitative findings reveal that contextualized speaking tasks and authentic interaction fostered greater engagement and communicative risk-taking. The study confirms that communicative competence development requires integration of linguistic knowledge, sociocultural awareness, and emotional readiness. The results suggest that real-life simulation and multimodal communication tasks effectively promote “fluent and fearless” English use. Pedagogical implications highlight the importance of structured communicative environments that prioritize authentic use rather than grammatical accuracy alone.